2020
DOI: 10.1002/cam4.3279
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of universal Lynch syndrome screening in a publicly funded healthcare system

Abstract: Purpose Referrals for Lynch syndrome (LS) assessment have traditionally been based on personal and family medical history. The introduction of universal screening practices has allowed for referrals based on immunohistochemistry tests for mismatch repair (MMR) protein expression. This study aims to characterize the effect of universal screening in a publicly funded healthcare system with comparison to patients referred by traditional criteria, from January 2012 to March 2017. Methods Patient files from the tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Our observed MMR mutation prevalence falls within the published range of 2–6% amongst unselected ECs [ 2 , 3 , 4 , 5 , 6 ] but is nonetheless at the higher end of the range compared to most universal screening studies employing either MSI and/or IHC [ 4 , 27 , 37 , 38 ]. This could be due to differences in the types of PVs identified by MSI vs. IHC, a higher-than-average rate of LS among our study cohort (the MUHC is a university teaching hospital, perhaps serving a higher-risk population), an increase in the number of individuals missed by other two-step screening protocols (MSI then IHC, or IHC then MSI), differences in IHC efficacy between centers, or the fact that 16 out of 17 patients referred for genetic counselling in our study ultimately consented to genetic testing, as compared to higher rates of drop-out/decline of testing in other published studies [ 29 , 37 , 38 ].…”
Section: Discussion Of Limitationsmentioning
confidence: 90%
See 1 more Smart Citation
“…Our observed MMR mutation prevalence falls within the published range of 2–6% amongst unselected ECs [ 2 , 3 , 4 , 5 , 6 ] but is nonetheless at the higher end of the range compared to most universal screening studies employing either MSI and/or IHC [ 4 , 27 , 37 , 38 ]. This could be due to differences in the types of PVs identified by MSI vs. IHC, a higher-than-average rate of LS among our study cohort (the MUHC is a university teaching hospital, perhaps serving a higher-risk population), an increase in the number of individuals missed by other two-step screening protocols (MSI then IHC, or IHC then MSI), differences in IHC efficacy between centers, or the fact that 16 out of 17 patients referred for genetic counselling in our study ultimately consented to genetic testing, as compared to higher rates of drop-out/decline of testing in other published studies [ 29 , 37 , 38 ].…”
Section: Discussion Of Limitationsmentioning
confidence: 90%
“…Recently, Lee et al evaluated the efficiency of IHC screening for LS in a Vancouver population, and found that the implementation of universal screening increased efficiency in detecting LS. They suggested that secondary screening, including BRAF and MLH1 promoter hypermethylation testing, could further increase cost-effectiveness in a universal healthcare system [ 29 ]. Our goal was to therefore contribute to the existing literature regarding the feasibility and performance of a universal IHC screening program for all newly diagnosed ECs within a single Canadian university hospital setting.…”
Section: Identifying Individuals With Lynch Syndrome: Old and New mentioning
confidence: 99%
“…Universal MMR screening programs have been demonstrated to increase detection of Lynch syndrome although outcome and efficiency is influenced by age groups including screening strategy, completeness of analyses and successful prevention of CRC-related mortality in individuals at increased risk [ 9 , 10 , [22] , [23] , [24] ]. Clinical implementation, however, varies between countries and institutions and is sometimes restricted e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of PofO information due to parents being unavailable, deceased, or declining genetic testing, cascade genetic testing must be offered to both sides of the family until segregation is confirmed. This may be costly and burdensome to patients and families, exacerbating already low rates of uptake of cascade genetic testing 19,20 . Eliminating the need to test one side of the family is a clear benefit and a major clinical utility of defining PofO for pathogenic variants, and more broadly, establishing chromosome-length haplotypes with accurate parental segregation of genomic variation has widespread applications.…”
Section: Introductionmentioning
confidence: 99%